KIGO PADA HAIKU KOBAYASHI ISSA DALAM PERSPEKTIF SEMIOTIKA C.S. PIERCE - Dian Setyowati (Universitas 17 Agustus 1945 Surabaya, 2010)
Abstract. The focus of this research are the types of kigo, kigo semiotic meaning, and message in-haikus written by Kobayashi Issa from the perspective of Charles Sanders Pierce’s semiotics. Some conclusions can be drawn as follows:1) the types of kigo are jiko, tenmon, gyouji, seikatsu, doubutsu, and shokubutsu; 2) the kigo semiotic meanings are: suzushisa symbolizes 'peace of mind'; Haruis an index of 'atmosphere to expect'; Meigetsu symbolizes 'evil that can not be covered'; Aki no ame symbolizes 'sorrow'; Yuki is the symbol of 'silent condition'; Yukige is the symbol of gawa ' freedom '; Neshaka is an icon for ' patience '; Hotoke is an icon for ' model for his people '; Koromogae symbolizes ' steady state '; Kaibushi symbolizes ' finite state '; Kawazu is the symbol of “joy '; Chou symbolizes 'freedom and happiness'; Yanagi is the symbol of 'parents who educate their children'; Yuuzakura is the symbol of 'sincerity of heart'; 3) the messages are: (a) Human beings should be grateful. (b) To maintain the dignity, human beings must be resolute. (c) wrongdoing can not be covered. (d) Men must always have hope. (e) Every human being has the right to have a free life. (f) Do not restrain the freedom of others. (g) Humans should be able to be patient. (h) the Buddha's patience is a role model for his people. (i) Human beings must strive for a better life. (k) Utilize the best of this short life. (l) Being alone does not mean sadness. (m) Parents must educate their children. (n) Man must be humble. Kata kunci: haiku, keigo, semiotik, ikon, indeks, simbol